Chemical constituents of Paratinospora sagittata and their chemotaxonomic significance - Wei Nie; Zhang-Juan Li; Ye-Ting Shi; Ming Hu; Xing-De Wu; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Plant growth patterns serve as a power switch governing microbial N use efficiency and N2O emission in an alpine meadow under climate change on the Qinghai-Tibet Plateau - Zheng Li; Yubao Sha; Huihui Liu; Guozheng Hu; Fen Zhao; Hasbagan Ganjurjav; Qingzhu Gao (Agriculture, Ecosystems & Environment, 2026)

Allergens and allergenicity in cell-cultured meat: Current status and reflections - Yun Li; Fen Jin; Yongzhong Qian; Shouwei Wang; Shijie Ding; Yingying Li; Lei Hu; Runrun He; Yuru Yan; Tianyi Tao; Meijuan Bo (Trends in Food Science & Technology, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Ship hydrodynamic optimization for minimum resistance through an improved grey wolf algorithm and ship model experimental verification - Jie Liu; Li-fen Hu; Bao-ji Zhang; Yong-yi Jiang; Jun-ying Bi; Ying-kai Dong; Guo-hua Yan (Ocean Engineering, 2026)

Reassessing the efficacy and safety of trimethoprim-sulfamethoxazole for Pneumocystis jirovecii pneumonia: a retrospective study - Yangmin Hu; Wei Hu; Danyang Li; Fen Lan; Wei He; Meng Chen; Difei Yao; Junjun Xu; Yujin Lai; Haibin Dai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Anti-MRSA and cytotoxic activity of a new diamide compound isolated from Aspergillus sp. H30 - Long-Fen Li; Ying-Ying Hu; Xin-Zhu Wang; Qing-Zhou Meng; Pei-Pei Zhao; Qiao-Ni Chen; Ying Xu; Xue-Kui Xia (Natural Product Research, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Structure-driven transparent and self-healing polyimides for durable flexible low-E window films - Fen Zhao; Xiwei Mo; Yulin Li; Yunkang Luo; Jianqiao Zhao; Zhaoshi Yu; Heng Xu; Hao Huang; Bin Hu; Guoli Tu (Chemical Engineering Journal, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Monitoring the level of hydrogen sulfide in arthritis and its treatment with a novel near-infrared fluorescent probe - Jing-Jing Chao; Ling Hu; Jing-Fang Mi; Guo-Jiang Mao; Fen Xu; Liufang Hu; Juan Ouyang; Chun-Yan Li (Analytica Chimica Acta, 2025)

Three new isoquinoline alkaloids from the fermentation of Aspergillus sp. 0338 and their anti-MRSA activities - Min Yang; Miao Dong; Qing-Yang Wu; Shui Yao; Gui Pu; Yue-Yu Ma; Rui-Feng Xiong; Qiu-Fen Hu; Fang Wang; Yin-Ke Li (Natural Product Research, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Numerical study of set-up effects on axial capacity of jacked piles in saturated clay - Zihang Li; Dan Hu; Fen Li; Wenlin Xiong (Ocean Engineering, 2024)

Efficiency and mechanism of sludge thickening by a novel sandwich-like forward osmosis composite membrane constructed on microporous polyethylene separator - Fen Chen; Jingyuan Yu; Jintai Hu; Guoqing Zhang; Chunhui Du; Xuchun Li (Chemical Engineering Journal, 2024)

Two-way coupling fluid–structure interaction analysis on dynamic response of offshore wind turbine - Fen Li; Jiaojiao Fu; Jiahui Chen; Dan Hu (Marine Georesources & Geotechnology, 2024)

A comparison of the physicochemical properties, allergenicity, and stability of recombinant β-lactoglobulin: Development of standard bovine milk allergens - Fen Xie; Wei Hu; Xuanyi Meng; Chunqiu Hu; Xin Li; Hongbing Chen (Food Bioscience, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Quantitative differentiation of toxicity contributions and predicted global risk of fipronil and its transformation products to aquatic invertebrates - Fen Liu; Huizhen Li; Xiaolei Zhang; Hao Hu; Biyao Yuan; Jing You (Water Research, 2024)

Analysis of blood biochemistry and non-targeted metabolomics of endometritis in dairy cows - Guoshang Ji; Junxing Zhang; Xue Feng; Hui Sheng; Honghong Hu; Fen Li; Yanfen Ma; Yamei Hu; Rina Na; Wenfei Yang; Yun Ma (Animal Reproduction Science, 2024)

Microcystin-LR and polystyrene microplastics jointly lead to hepatic histopathological damage and antioxidant dysfunction in male zebrafish - Wang Lin; Fen Hu; Fang Liu; Ling Liao; Ling Ling; Li Li; Jifeng Yang; Pinhong Yang (Environmental Pollution, 2024)

Study on the coupled and coordinated development of urban resilience and urbanization level in the Yellow River Basin - Haiyang Li; Chenxu Hu; Mengying Zhu; Jiarong Hong; Zhaojun Wang; Fen Fu; Jiaqi Zhao (Environment, Development and Sustainability, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Effect of exposures to multiple metals on blood pressure and hypertension in the elderly: a community-based study - Wen-lei Hu; Wei Xiao; Wen-bin Shen; Yue-yang Wu; Xue Li; Qi Zhong; Guo-ao Li; Huan-huan Lu; Jian-jun Liu; Zhi-hua Zhang; Fen Huang (BioMetals, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

The combined effects of exposure to multiple PM2.5 components on overweight and obesity in middle-aged and older adults: a nationwide cohort study from 125 cities in China - Xue Li; Yueyang Wu; Guoao Li; Wenbin Shen; Wei Xiao; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (Environmental Geochemistry and Health, 2023)

The impact of multiple metals exposure on the risk of developing proliferative diabetic retinopathy in Anhui, China: a case–control study - Yan-Qing Li; Si-Tian Zhang; Nai-Yu Ke; Yan-Cheng Fang; Wen-Lei Hu; Guo-Ao Li; Fen Huang; Yan-Feng Zhou (Environmental Science and Pollution Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

Influence of dissolved organic carbon on multimedia distribution and toxicity of fipronil and its transformation products in lotic waterways - Weizong Li; Hao Hu; Fen Liu; Huizhen Li; Jing You (Journal of Environmental Sciences, 2023)

pH-Regulated lignin as a green catalyst for Highly-Efficient CO2 cycloaddition - Yidan Ouyang; Bin Lei; Zhouqing Tan; Fen Hu; Zhao Wu; Jiaxue Wang; Yixuan Ma; Ran Zhang; Li Guo; Feifei Chen (Fuel, 2023)

Identification and protective role of CD34+ stromal cells/telocytes in experimental autoimmune encephalomyelitis (EAE) mouse spleen - Ganesh Dama; Xiaoxi Hu; Yushan Yan; Yonghai Li; Han Li; Fen Yang; Yanli Liu; Juntang Lin (Histochemistry and Cell Biology, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Isochromenes from the Nicotiana tabacum -derived endophytic fungus Aspergillus versicolor and their anti-tobacco mosaic virus activities - Feng-Xian Yang; Jia-Meng Dai; Hua-Yin Liu; Qi-Li Mi; Jin Wang; Jian-Duo Zhang; Xue-Mei Li; Wei-Guang Wang; Min Zhou; Yin-Ke Li; Qiu-Fen Hu (Natural Product Research, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

The anti-TMV potency of the tobacco-derived fungus Aspergillus versicolor and its active alkaloids, as anti-TMV activity inhibitors - Jia-Meng Dai; Qi-Li Mi; Xue-Mei Li; Du Gang; Guang-Yu Yang; Jian-Duo Zhang; Jin Wang; Yin-Ke Li; Hai-Ying Yang; Dong Miao; Zhen-Jie Li; Qiu-Fen Hu (Phytochemistry, 2023)

Association of exposure to multiple serum metals with the risk of chronic kidney disease in the elderly: a population-based case–control study - Wenlei Hu; Guoao Li; Jialiu He; Huanhuan Zhao; Hanshuang Zhang; Huanhuan Lu; Jianjun Liu; Fen Huang (Environmental Science and Pollution Research, 2022)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Outdoor air pollution enhanced the association between indoor air pollution exposure and hypertension in rural areas of eastern China - Guoao Li; Huanhuan Lu; Wenlei Hu; Jianjun Liu; Mingjun Hu; Jialiu He; Fen Huang (Environmental Science and Pollution Research, 2022)

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

The behavior of monopile embedded in sand under scour and cyclic loading conditions - Fen Li; Zhiyuan Zhu; Peisan Tian; Dan Hu; Yifan Li (Marine Georesources & Geotechnology, 2022)

Exposure to 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol and risk of thyroid cancer: a case-control study in China - Wan-Jun Yang; Hua-Bing Wu; Chi Zhang; Qi Zhong; Ming-Jun Hu; Jia-Liu He; Guo-Ao Li; Zhen-Yu Zhu; Jin-Liang Zhu; Huan-Huan Zhao; Han-Shuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2021)

Associations between essential microelements exposure and the aggressive clinicopathologic characteristics of papillary thyroid cancer - Ming-Jun Hu; Jia-Liu He; Xin-Ran Tong; Wan-Jun Yang; Huan-Huan Zhao; Guo-Ao Li; Fen Huang (BioMetals, 2021)

Migration of mineral oil hydrocarbons from food contact papers into food simulants and extraction from their raw materials - Jing Jing Pan; Yan Fen Chen; Jian Guo Zheng; Changying Hu; Dan Li; Huai Ning Zhong (Food Additives & Contaminants: Part A, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Neuronal Activity in the Cerebellum During the Sleep-Wakefulness Transition in Mice - Li-Bin Zhang; Jie Zhang; Meng-Jia Sun; Hao Chen; Jie Yan; Fen-Lan Luo; Zhong-Xiang Yao; Ya-Min Wu; Bo Hu (Neuroscience Bulletin, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Does dual reduction in chemical fertilizer and pesticides improve nutrient loss and tea yield and quality? A pilot study in a green tea garden in Shaoxing, Zhejiang Province, China - Shaowen Xie; Hanxiao Feng; Fen Yang; Zhide Zhao; Xuedi Hu; Chaoyang Wei; Tao Liang; Haitao Li; Yuanbo Geng (Environmental Science and Pollution Research, 2019)

Transcriptome analysis of Hevea brasiliensis in response to exogenous methyl jasmonate provides novel insights into regulation of jasmonate-elicited rubber biosynthesis - Jin-Ping Liu; Jin Hu; Yan-Hui Liu; Cui-Ping Yang; Yu-Fen Zhuang; Xiu-Li Guo; Yi-Jian Li; Liangsheng Zhang (Physiology and Molecular Biology of Plants, 2018)

Minimally Toxic Dose of Lipopolysaccharide and α-Synuclein Oligomer Elicit Synergistic Dopaminergic Neurodegeneration: Role and Mechanism of Microglial NOX2 Activation - Wei Zhang; Jun-hua Gao; Zhao-fen Yan; Xi-yan Huang; Peng Guo; Li Sun; Zhuo Liu; Yang Hu; Li-jun Zuo; Shu-yang Yu; Chen-Jie Cao; Xiao-min Wang; et al. (Molecular Neurobiology, 2018)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

A New Perspective for Parkinson’s Disease: Circadian Rhythm - Siyue Li; Yali Wang; Fen Wang; Li-Fang Hu; Chun-Feng Liu (Neuroscience Bulletin, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil - Lin Huang; Xian-yong Ma; Zong-yong Jiang; You-jun Hu; Chun-tian Zheng; Xue-fen Yang; Li Wang; Kai-guo Gao (Journal of Zhejiang University-SCIENCE B, 2016)

Genes encoding Δ8-sphingolipid desaturase from various plants: identification, biochemical functions, and evolution - Shu-Fen Li; Guo-Jun Zhang; Xue-Jin Zhang; Jin-Hong Yuan; Chuan-Liang Deng; Zan-Min Hu; Wu-Jun Gao (Journal of Plant Research, 2016)

Feeding ecology of the mud shrimp S olenocera melantho in the E ast C hina S ea - Hui Yu Li; Jian Zhong Ling; Li Ping Yan; Jia Hua Cheng; Fen Hu (Marine Ecology, 2016)
The feeding habits of the mud shrimp Solenocera melantho were studied in the East China Sea by analysing 720 stomach contents and comparing diet composition and prey diversity among seasons, sexes and size classes. Feeding activity was linked to season and ovarian condition. The stomach fullness was high during spring and summer and low in fall. Females with advanced ovaries also displayed low stomach fullness, which suggests that feeding activity is affected by the reproductive cycle. The diet of S. melantho consisted of 42 different prey categories, primarily smaller crustaceans, Foraminifera, polychaetes, mollusks and fishes (larvae and eggs). Crustacea,Foraminifera and polychaetes together constituted the dominant prey groups, accounting for 75% of total prey abundance and >50% of total prey occurrence. Diet composition differed among seasons between sexes and size classes. Females and males consumed the same prey items but with different orders of importance. In terms of body size, the small shrimps preferred relatively small food items, such as Foraminifera and algae, whereas larger shrimps preferred polychaetes and crustaceans. Trophic diversity varied among the seasons within both sexes and size classes, with the highest values being observed in fall. Niche overlap was high within both sexes and size classes among seasons (0.6051–0.8740).

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Identification of intestinal bacterial flora in Rhipicephalus microplus ticks by conventional methods and PCR–DGGE analysis - Xing-Li Xu; Tian-Yin Cheng; Hu Yang; Fen Yan (Experimental and Applied Acarology, 2015)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

Microsatellite markers reveal genetic diversity of wild soybean in different habitats and implications for conservation strategies (Glycine soja) in China - Ke-Jing Wang; Xiang-Hu Li; Mao-Fen Yan (Conservation Genetics, 2014)

Three homologous genes encoding functional ∆8-sphingolipid desaturase in Populus tomentosa - Shu-Fen Li; Guo-Jun Zhang; Ying-Chun Yuan; Cong-Hui Wang; Wu-Jun Gao; Chuan-Liang Deng; Long-Dou Lu; Zan-Min Hu (Genes & Genomics, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

The role of sucrose-metabolizing enzymes in pear fruit that differ in sucrose accumulation - Hu Ping Zhang; Ju You Wu; Gai Hua Qin; Gai Fang Yao; Kai Jie Qi; Li Fen Wang; Shao Ling Zhang (Acta Physiologiae Plantarum, 2014)

Response Surface Method of Reliability Analysis and its Application in Slope Stability Analysis - Xiao-hui Tan; Meng-fen Shen; Xiao-liang Hou; Dan Li; Na Hu (Geotechnical and Geological Engineering, 2013)

Probiotic Bacillus amyloliquefaciens mediate M1 macrophage polarization in mouse bone marrow-derived macrophages - Jian Ji; Sheng-Lan Hu; Zhi-Wen Cui; Wei-Fen Li (Archives of Microbiology, 2013)

Time-Variant Reliability Analysis of Unsaturated Soil Slopes Under Rainfall - Xiao-hui Tan; Na Hu; Dan Li; Meng-fen Shen; Xiao-liang Hou (Geotechnical and Geological Engineering, 2013)

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Genome of alkaliphilic Bacillus pseudofirmus OF4 reveals adaptations that support the ability to grow in an external pH range from 7.5 to 11.4 - Benjamin Janto; Azad Ahmed; Masahiro Ito; Jun Liu; David B. Hicks; Sarah Pagni; Oliver J. Fackelmayer; Terry‐Ann Smith; Joshua Earl; Liam D.H. Elbourne; Karl Hassan; Ian T. Paulsen; et al. (Environmental Microbiology, 2011)
Summary Bacillus pseudofirmus OF4 is an extreme but facultative alkaliphile that grows non‐fermentatively in a pH range from 7.5 to above 11.4 and can withstand large sudden increases in external pH. It is a model organism for studies of bioenergetics at high pH, at which energy demands are higher than at neutral pH because both cytoplasmic pH homeostasis and ATP synthesis require more energy. The alkaliphile also tolerates a cytoplasmic pH > 9.0 at external pH values at which the pH homeostasis capacity is exceeded, and manages other stresses that are exacerbated at alkaline pH, e.g. sodium, oxidative and cell wall stresses. The genome of B. pseudofirmus OF4 includes two plasmids that are lost from some mutants without viability loss. The plasmids may provide a reservoir of mobile elements that promote adaptive chromosomal rearrangements under particular environmental conditions. The genome also reveals a more acidic pI profile for proteins exposed on the outer surface than found in neutralophiles. A large array of transporters and regulatory genes are predicted to protect the alkaliphile from its overlapping stresses. In addition, unanticipated metabolic versatility was observed, which could ensure requisite energy for alkaliphily under diverse conditions.

A risk-associated single nucleotide polymorphism of SMAD7 is common to colorectal, gastric, and lung cancers in a Han Chinese population - Xin Li; Xue-xi Yang; Ni-ya Hu; Jing-zhe Sun; Fen-xia Li; Ming Li (Molecular Biology Reports, 2011)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Effects of Lactobacillus buchneri and Lactobacillus plantarum on fermentation, aerobic stability, bacteria diversity and ruminal degradability of alfalfa silage - Tao Zhang; Lei Li; Xiao-fen Wang; Zhao-hai Zeng; Yue-gao Hu; Zong-jun Cui (World Journal of Microbiology and Biotechnology, 2009)

Influence of N-Terminal Truncations on the Functional Expression of Bacillus licheniformis γ-Glutamyltranspeptidase in Recombinant Escherichia coli - Long-Liu Lin; Li-Yu Yang; Hui-Yu Hu; Huei-Fen Lo (Current Microbiology, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)